Improvement microstrip patch antenna for ultra-wideband by C-shaped wide slot - Satthamsakul, S.; Puntheeranurak, S.; Benjankaprasert, C.; Anantrasirichai, N.; Wakabayashi, T. (My University, 2010)
The simple rectangular patch antenna is designed at frequency 7 GHz and matched impedance with 50 ohms of transmission line. The technique to achieved widest bandwidth from 3 GHz to 12 GHz coverage standard of UWB applications is proposed by etches out slot on the ground plane with inset technique. The configuration and the size of slot on the ground plane are important to enhanced bandwidth, and inset feed is used for good impedance matching in wide frequency range. The radiation patterns of each frequency show the bi-directional with null at angle ±90°. ©ICROS.
Keywords: Inset; Patch; Radiation pattern; Slot; UWB antenna